KARAKTERISTIK HABITAT KATAK CAPAPUYA Barbouroula kalimantanensis (Iskandar, 1978) (AMFIBIA: ANURA) DI DUA SUB-DAS MELAWI KALIMANTAN BARAT - Wijaya, Syuryadi; Junardi, Junardi; Riyandi, Riyandi (Jurnal Protobiont, 2020)
Capapuya or Barbourula kalimantanensis is an endemic lungless frog in Borneo that live in water, but data on this frog's habitat is still very limited. This study aims to obtain data on habitat characteristics and in the Melawi sub-watershed, namely the Mentatai and Ella stream. The research was conducted in August-December 2019. Each location is divided into three stations with each station divided into three points. Data were collected during the day and night by measuring the characteristics of water, vegetation, and recording temperature and humidity. The results of this study found three individuals of B. kalimantanensis in the Mentatai and one individual in the Ella stream. The habitat of B. kalimantanensis in the Mentatai and Ella stream is characterized by a rocky substrate, shallow water (<1 m), high dissolved oxygen content, low carbon dioxide content and riparian vegetation dominated by Dipterocarpace.